Contribution to the knowledge of the distribution of the rare orchid Epipogium aphyllum Swartz in Bosnia and Herzegovina - Srđan Brujić (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
In 2020, a new site of the ghost orchid (Epipogium aphyllum Swartz) was found in the area of Mt. Jadovnik, near Drvar in the western part of Bosnia and Herzegovina. This mycoheterotrophic orchid belongs to one of the rarest and least known species of orchids in the world. The paper gives a brief description of the ecology of the species, a description of the habitat conditions in the site area, and an overview of the previous records for Bosnia and Herzegovina. It was found in beech and fir dominated primeval forest, in Visućka draga on Mt. Jadovnik. So far, it has been confirmed in only a few locations in Bosnia and Herzegovina.